2021
DOI: 10.1177/10781552211031304
|View full text |Cite
|
Sign up to set email alerts
|

A possible interaction between favipiravir and methotrexate: Drug-induced hepatotoxicity in a patient with osteosarcoma

Abstract: Introduction Favipiravir is an antiviral agent that is recently used for SARS-CoV2 infection. The drug-drug interactions of favipiravir especially with chemotherapeutic agents in a patient with malignancy are not well known. Case report The patient diagnosed with metastatic osteosarcoma was given high dose methotrexate treatment, and favipiravir was started on the third day of the treatment with suspicion of SARS-CoV2 infection. Grade 3 hepatotoxicity developed after favipiravir. Management & outcome: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…Therefore, it can be thought that the inhibitory effect against AO decreases depending on the decrease in blood concentrations of drugs that inhibit AO (4). Demir et al suggested that favipiravir may inhibit methotrexate elimination by inhibiting aldehyde oxidase (13). Contrary to expectations, we found that when favipiravir was coadministered with verapamil, an AO inhibitor, Cl increased and t 1/2 , MRT, C max, and AUC values decreased.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be thought that the inhibitory effect against AO decreases depending on the decrease in blood concentrations of drugs that inhibit AO (4). Demir et al suggested that favipiravir may inhibit methotrexate elimination by inhibiting aldehyde oxidase (13). Contrary to expectations, we found that when favipiravir was coadministered with verapamil, an AO inhibitor, Cl increased and t 1/2 , MRT, C max, and AUC values decreased.…”
Section: Discussioncontrasting
confidence: 99%
“…Favipiravir is extensively metabolized to an inactive metabolite favipiravir-M1 (F-M1) by AO and lesser extent by XO in the liver and excreted by the renal route (11)(12)(13). Cytochrome P450 isoenzymes do not contribute to the metabolism of favipiravir (4,11).…”
Section: Discussionmentioning
confidence: 99%
“…Failure to sufficiently characterize AO mediated metabolism has led to inaccurate predictions of clearance resulting in either toxicity or poor exposure in humans, leading to discontinuation of compounds such as carbazeran, BIBX1382, FK3453, LuAF09535, and RO1 (Akabane et al, 2011;Dittrich et al, 2002;Jensen et al, 2017;Kaye et al, 1984. Recent reports such as methotrexate-induced liver toxicity due to inhibition of its metabolism following co-administration of an AO substrate and inhibitor, favipiravir (Demir et al, 2022) also indicate the possible role of AO in clinically significant drug-drug interactions (DDIs). AO shows wide species differences which makes the translation of toxicological data challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports such as methotrexateinduced liver toxicity due to inhibition of its metabolism following coadministration of an AO substrate and inhibitor, favipiravir, also indicate the possible role of AO in clinically significant drug−drug interactions (DDIs). 37 Anti-infective agents like famciclovir are approved for the treatment of opportunistic infections (herpes simplex virus, varicella zoster) in HIV-infected adolescents and are also recommended for HIV-infected children. 38 Low therapeutic index oncology drugs such as 6-mercaptopurine and methotrexate are metabolized partly by AO and are administered to children.…”
Section: Discussionmentioning
confidence: 99%